ANALISIS PERAN BIMBINGAN ORANG TUA TERHADAP PRESTASI BELAJAR SISWA KELAS V SD NEGERI 30 PUNCAK CENDERAWASIH KOTA SORONG - Maria Agnes Nauw; Abddulrahman Hatsma; Desti Rahayu (CV. ADIBA ASIHA AMIRA, 2025)
Parents' attention to children's education in the household greatly determines the success of children in learning. This has a positive impact on behavioral changes and children's educational development. Parents must always pay attention to how their children learn at home so that their children get good achievements at school. The learning difficulties experienced by students are inseparable from the role of parents in providing guidance at home. The role of parents towards children is often influenced by the attitude of parents in providing guidance and coaching to children. The purpose of this study is to be able to find out the role of parental guidance on the learning achievement of grade V students of SD Negeri 30 Puncak Cenderawasih Kota Sorong and to be able to find out the factors that affect the learning achievement of grade V students of SD Negeri 30 Puncak Cenderawasih Sorong City. This study uses a qualitative approach, with the method used in this study being qualitative descriptive. The results of the study show that the role of parental guidance for learning achievement of students of Class V SD Negeri 30 Puncak Cenderawasih Sorong City, there are four parents who have not provided learning assistance to their children, and one parent has not fully provided learning assistance to their children, and two parents have not provided learning assistance to their children because parents are busy in their daily lives so that students have not received full learning assistance from parents. There are three roles of parental guidance on the learning achievement of Class V students of SD Negeri 30 Puncak Cenderawasih Sorong City, namely parents as student companions, parents as facilitators, and parents as student motivators. Factors that hinder tutoring activities from parents to children are such as parents who do not understand the material being studied by their children, a crowded home environment that is not conducive, and subject matter that is not clear or even absent in textbooks.